2010
DOI: 10.1085/jgp.200910397
|View full text |Cite
|
Sign up to set email alerts
|

IP3-dependent, post-tetanic calcium transients induced by electrostimulation of adult skeletal muscle fibers

Abstract: Tetanic electrical stimulation induces two separate calcium signals in rat skeletal myotubes, a fast one, dependent on Cav 1.1 or dihydropyridine receptors (DHPRs) and ryanodine receptors and related to contraction, and a slow signal, dependent on DHPR and inositol trisphosphate receptors (IP3Rs) and related to transcriptional events. We searched for slow calcium signals in adult muscle fibers using isolated adult flexor digitorum brevis fibers from 5–7-wk-old mice, loaded with fluo-3. When stimulated with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(81 citation statements)
references
References 67 publications
3
75
3
Order By: Relevance
“…At this stimulation frequency, an increase of TnIs and a decrease in TnIf mRNA levels take place (Casas et al, 2010), a characteristic feature of fast-to-slow fiber phenotype transition.…”
Section: Introductionmentioning
confidence: 98%
“…At this stimulation frequency, an increase of TnIs and a decrease in TnIf mRNA levels take place (Casas et al, 2010), a characteristic feature of fast-to-slow fiber phenotype transition.…”
Section: Introductionmentioning
confidence: 98%
“…In normal adult mice skeletal muscle, we observed that IP 3 R immuno-labeling follows distinctive patters resembling the SR (types 1, 2 and 3 IP 3 Rs), sarcolemmal (types 1 and 3 IP 3 Rs) or nuclear localizations (types 1 and 3 IP 3 Rs) (Casas et al 2010). The labeling for both type 1 and type 2 IP 3 Rs subtypes showed a fiber type-specific distribution with much higher expression in fast (type II) muscle fibers, whereas type 3 IP 3 R showed a uniform distribution in both fiber types, as shown by co-labeling with slow myosin heavy chain antibody.…”
Section: Alterations In Both Ip 3 Rs and E-t Coupling In Dmd Modelsmentioning
confidence: 81%
“…IP 3 mediated Ca 2+ signals induce both a transient activation of ERK½ and transcription factor CREB, and an increase in early genes (c-fos, c-jun and egr-1) and in late genes (troponin I, interleukin-6, hmox and hsp70) mRNA levels after depolarization of normal skeletal muscle cells Juretic et al 2006;Juretic et al 2007;Jorquera et al 2009). Moreover, in electrically stimulated adult muscle fibers, slow Ca 2+ signals mediate the frequency-dependent activation of slowphenotype muscle fiber genes (slow troponin I, TnIs) and repression of fast-phenotype ones (TnIf) (Casas et al 2010). These evidences link slow Ca 2+ transients with muscular effects of nerve activity and with the process of muscle cell plasticity.…”
Section: Excitation-transcription (E-t) Couplingmentioning
confidence: 96%
See 1 more Smart Citation
“…It should be mentioned though that this does not exclude the potential for Ins(1,4,5)P 3 to be involved in Ca 2+ signals with a physiological purpose other than contraction, either in a voltage-dependent (Casas et al, 2010;Jorquera et al, 2013) or voltage-independent manner (Tjondrokoesoemo et al, 2013). On the other hand, considering the growing number of proteins and specifically of voltage-dependent and voltage-independent ion channels that are sensitive to the PtdIns(4,5)P 2 level in the plasma membrane, it was of strong interest to investigate whether the function of the E-C coupling molecular machinery would be dependent on PtdIns(4,5)P 2 level.…”
Section: Confocal Imagingmentioning
confidence: 95%